Paws, probes, and PCR: Unraveling the clinical jigsaw puzzle of Bartonella henselae infection - Zainulabid, Ummu Afeera; Ramli, Siti Roszilawati; Jaafar, Rohaizam; Kamarudin, Nurul Akmal; May, Ling Ong; Saw, Yen Tsen; Yeow, Yong Yaw; Ravintharan, Sheena Kristil; Khalid, Khairil Erwan; Leong, Chee Loon (2024)
In immunocompromised individuals presenting with pyrexia of unknown origin, Bartonella spp. infection warrants specific diagnostic consideration. Our case underscores the significance of probing into a patient's history, particularly past exposures to cats, as a crucial step in unraveling complex clinical scenarios. Notably, despite negative serological findings, a definitive diagnosis in our case was achieved through molecular techniques, highlighting the indispensable role of PCR. This instance emphasizes the critical importance of molecular tools, specifically PCR, in navigating intricate and uncommon presentations of Bartonella spp. infection.